2013
DOI: 10.11648/j.ajns.20130203.13
|View full text |Cite
|
Sign up to set email alerts
|

Developing Smoking Cessation Program for Older Canadian People: An Application of Precede-Proceed Model

Abstract: Precede-Proceed model is a flexible and appropriate to develop a smoking cessation/prevention program. The main purpose of this paper is to develop a preliminary hypothetical health promotion program that is focused on smoking cessation / prevention for older Canadian people who smoke and live in nursing homes to improve their quality of life. It is hoped that advanced-practice gerontology nurses in a range of health settings will be able to gain insights from this paper to help older Canadian people who smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In phase 4, the predisposing factors (including information, attitudes, beliefs, values, and perception about the desired behavior change), enabling factors (including the contextual factors that facilitate or hinder the desired behavioral and environmental changes), and reinforcing factors (rewards and evaluation of others that may encourage or discourage continuing the desired behavior change) are identified. [ 14 ] In one study in China, Li et al . showed that this model can be used as an effective tool for identification community health needs.…”
Section: Introductionmentioning
confidence: 99%
“…In phase 4, the predisposing factors (including information, attitudes, beliefs, values, and perception about the desired behavior change), enabling factors (including the contextual factors that facilitate or hinder the desired behavioral and environmental changes), and reinforcing factors (rewards and evaluation of others that may encourage or discourage continuing the desired behavior change) are identified. [ 14 ] In one study in China, Li et al . showed that this model can be used as an effective tool for identification community health needs.…”
Section: Introductionmentioning
confidence: 99%